Neoplasias melanocíticas uveais em cães e gatos: aspectos morfológicos e imuno-histoquímicos - Matheus Vilardo Lóes Moreira (2020)
The most frequent lesions involving the eye are of neoplastic nature and melanocytic lesions are the most common in the uvea of dogs and in the iris of cats. They can be classified as melanocytomas (benign) and melanomas (malignant). For a better understanding of the biological behavior of uveal melanocytic neoplasms in dogs and cats, histological and immunohistochemical tools were applied to 32 eyes, 27 from dogs and five from cats. The ocular neoplasms of these animals were classified as benign (19/27 - dogs) or malignant (8/27 - dogs; 5/5 - cats), and the location of the involved ocular structures was described. The cell types of these neoplasms were also determined, including epithelioid, spindle and mixed, as well as special types, such as balloon cells, multinucleated giant cells and signet rings cells. In addition, the percentage of cells with melanin, the intensity of melanin within the cells, anisocytosis and anisokaryosis, the mitotic index, the presence of intratumoral inflammation and necrosis, vascular invasion and the development of secondary glaucoma were determined. To confirm the melanocytic origin, immunohistochemistry was performed with anti-PNL2 (29/32) and anti-melan-A (3/3) antibodies. The proliferative index in dogs was verified using the anti-Ki-67 antibody, which varied from 2.8 to 12% in melanocytomas, with an average of 6.45 ± 4.1 and from 15.8 to 70% in melanomas, with an average of 38.3 ± 25.21. The proliferative index for cats varied from 10.8 to 30.4%, with an average of 18.96 ± 7.36. The apoptotic index was also evaluated for both species, using the anti-caspase-3 antibody. For dogs, the apoptotic index varied from 3.8 to 50% in melanocytomas, with an average of 16.62 ± 13.26 and from 30 to 84% in melanomas, with an average of 58.04 ± 24.25. For cats, the apoptotic index ranged from 3.6 to 92%, with an average of 23.16 ± 38.62. The BAP1 protein, the marking pattern of which might influence tumor aggressiveness as reported for melanocytic ocular neoplasms in humans, was also evaluated in all uveal neoplasms in the present study. The histological and immunohistochemical characteristics found in uveal melanocytic neoplasms in dogs and cats in this study expanded the knowledge about the use of these tools as prognostic factors; however, further studies with animal survival follow-up after diagnosis are recommended.